Collaborative Governance Dalam Inovasi Layanan : Studi Pada Dukcapil Kabupaten Madiun Dengan PT POS Indonesia Dalam Program ANDOK (Antar Dokumen Kependudukan) di Kabupaten Madiun - Loren, Irananda Destiani; Pradana, Galih Wahyu (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The Department of Population and Civil Registration (Disdukcapil) of Madiun Regency is a Regional Apparatus Organization (OPD) responsible for delivering public services in the field of population administration and civil registration. In an effort to improve service quality, Disdukcapil Madiun has developed several innovations, one of which is the ANDOK service. ANDOK is a collaborative-based service innovation focused on the delivery of population documents in partnership with PT Pos Indonesia. In its implementation, Disdukcapil collaborates with the Main Branch Office (KCU) of PT Pos Indonesia in Madiun as its collaborative partner. This study aims to examine the mechanism of collaborative governance between Disdukcapil Madiun Regency and PT Pos Indonesia in the ANDOK service innovation. The findings show that the collaboration mechanism in the implementation of the ANDOK service runs effectively and meets the established indicators. Both institutions share a common vision, mission, and background, and demonstrate a strong commitment to improving effective and efficient public service delivery through this collaboration. Communication between stakeholders flows smoothly through both formal and informal channels. Decision-making is carried out through deliberation to achieve consensus. Each actor has a well-defined role, as outlined in the memorandum of understanding (MoU). The collaboration is conducted transparently and has achieved a high level of public satisfaction. However, a weakness was found in budget planning, resulting in the suspension of the ANDOK service each mid-year due to budget constraints